Effects of Digital Maternal Referral Systems on Referral Performance and Maternal Survival-Related Outcomes: A Systematic Review - Erni Suryani Wongso; Zulvayanti Zulvayanti; Hadi Susiarno (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Timely maternal referral is essential for emergency obstetric care, but the effectiveness of digital maternal referral systems in improving referral performance and maternal survival-related outcomes remains uncertain. This systematic review synthesized evidence on digital, mobile, or information-based referral interventions that have core functions comparable to those of integrated referral systems such as SISRUTE. Scopus and PubMed were searched for English-language records published from 1 January 2000 to 31 December 2025. The review followed PRISMA 2020 guidance. Eligible studies involved pregnant, intrapartum, or postpartum women, obstetric emergency referrals, or health workers managing maternal referrals, and evaluated implemented digital or mobile referral interventions. Studies limited to non-digital referral barriers, prototype development without evidence of implementation, or non-maternal referral populations were excluded. Owing to heterogeneity in design, interventions, and outcomes, narrative synthesis was conducted. Six studies from Uganda, Ghana, Liberia, and Iraq were included in the primary synthesis. Evidence for a reduction in direct maternal mortality was insufficient. However, digital referral interventions were associated with improved process and survival-related proxy outcomes, including lower adverse maternal-fetal outcomes, faster referral response, better identification of receiving hospitals, improved preparedness, and shorter decision-to-incision intervals for emergency cesarean delivery. The most consistent benefits were observed in communication, triage, coordination, and treatment timeliness. Digital maternal referral systems appear to be more strongly supported as tools for improving referral performance than as interventions with proven direct effects on mortality. Their potential contribution to maternal survival is most plausibly indirect and depends on transport, receiving-facility readiness, clinical triage, and implementation support Keywords: Digital health, e-referral, maternal referral, maternal survival, mHealth, obstetric emergency, triage